ADAPTIVE POTENTIAL AS A FACTOR IN THE TRANSFORMATION OF ENERGY SECTOR ENTERPRISES - Слободян, Назар Богданович; Дзьоба, Олег Григорович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The article examines the theoretical and practical foundations of the formation and development of the adaptation potential of enterprises in various spheres of activity, in particular, energy infrastructure enterprises. An analysis of modern trends in the field of energy and possible ways of development, aimed at increasing the adaptive potential of the energy sector to achieve the goals of sustainable development, was carried out. The essence of the concept of "adaptive potential of the enterprise" has been studied, the existing approaches to the interpretation of this term have been systematized and generalized, and the peculiarities of the formation and development of the adaptive potential of enterprises in the energy sector have been detailed. The importance and role of adaptation potential in the process of transformation of the energy sector in the conditions of climate change and existing energy trends has been updated. The authors analyze how the flexibility of the energy supply system, the speed of introduction of new technologies and strategies, as well as other aspects of adaptation can influence the paths and outcomes of energy transformation. Key aspects of adaptation of the energy sector to modern challenges and changes in the industry are considered. The study of the importance of adaptation potential in the process of energy transformation, taking into account the growth in the use of renewable energy sources and the need to reduce greenhouse gas emissions, was carried out. It has been established that hydrogen can play an important role in the transformation of the energy sector, but this requires significant investment and development of the relevant infrastructure and technologies. Prospects for further scientific research are determined, in particular, the need and importance of continuing scientific research in the direction of detailing individual components of the adaptation potential of energy enterprises, developing an economic mechanism for the formation, transformation and development of adaptation potential, synchronizing these processes with global transformation processes within the framework of the planetary energy transition.